Identification and comparison of the volatile constituents of fresh and dried leaves of Spondias mombin found in North-central Nigeria: in vitro evaluation of their cytotoxic and antioxidant activities. (1st November 2016) - Oladimeji, Abdulkabir Oladele; Aliyu, Medinat Bola; Ogundajo, Akintayo Lanre; Babatunde, Oluwatoyin; Adeniran, Oluremi Ishola; Balogun, Olaoye Solomon
Abstract: Context: Various studies have shown that the leaf extracts of Spondias mombin Linn (Anacardiaceae) possess pharmacological properties such as antioxidant and antiviral effects. However, no biological activity from its essential oil has been reported in literature. Objective: To analyse the chemical constituents, cytotoxic activity and antioxidant capability of the essential oils from fresh and dried leaves of S. mombin. Materials and methods: Hydrodistillation using Clevenger-type apparatus was employed to obtain the essential oil. Oil analysis was performed using an HP 6890 Gas Chromatograph coupled with an HP 5973 Mass Selective Detector. The cytotoxicity bioassay was carried out using the brine shrimp lethality test (10, 000–0.01 μg/mL). Additionally, the reactive oxygen species scavenging potential of the two S. mombin oils (1000–200 μg/mL) were investigated using a hydroxyl radical scavenging and ferric iron reducing system. Results: Chemical analysis of essential oils from S. mombin revealed the presence of 41 compounds, with predominance of monoterpenoids, sesquiterpenoids and non-terpenoids derivatives. In both fractions, the principal component was β-caryophellene (27.9–30.9%), followed by γ-cadinene (9.7–12.3%). There was an increase in the oxygenated monoterpenoid contents and a concomitant decrease in the amounts of sesquiterpenoids hydrocarbons observed on drying the leaves. The oil obtained from the fresh leaves was more active than that obtained from dried leaves, with LC50 values (from the brine shrimp lethality assay) of 0.01 and 4.78 μg/mL, respectively. The two oils (from fresh and dried leaves) at 1.0 mg/mL scavenged hydroxyl radical by 83% and 99.8%, respectively. Moreover, they reduced ferric ion significantly and compared favourably with vitamin C. Conclusions: Essential oil derived from the leaves of S. mombin could hold promise for future application in the treatment of cancer-related diseases.